Glomus mosseae promotes Xanthium italicum invasion - Tang, Jie Shi; Zhao, Zhi Long; Ma, Miao (Penerbit Universiti Kebangsaan Malaysia, 2020)
The relationship between mycorrhizal fungi and the invasiveness of alien plants is a controversial issue in plant invasion ecology. In this study, we investigated the influence of the mycorrhizal fungus Glomus mosseae on the physiological ecology, growth, and reproductive capacity of Xanthium italicum Moretti. We found that the relative chlorophyll content and net photosynthetic rate of the leaves of potted X. italicum whose rhizosphere soil was supplemented with G. mosseae was higher than those of the control group. Plants in the treatment group had longer root length and plant height; increased root, stem, and fruit biomass; and more male and female inflorescences and fruits relative to control plants. Additionally, the ratio of female to male inflorescence number was close to 2:1 in the treatment group as compared to 1:1 in the control group, suggesting an enhanced reproductive capacity in the former. G. mosseae applied to the soil also increased phosphorus absorption and accumulation in the roots, stems, and leaves of X. italicum. Thus, G. mosseae promotes the growth and reproduction of X. italicum and thereby enhances its competitiveness and capacity for colonizing a new habitat.